MiR-6858 plays a key role in the process of melatonin inhibition of the malignant biological behavior of glioma. (May 2021) - Wang, Chenglong; Zhao, Zhimin; Qi, Qichao; Wang, Jiwei; Kong, Yang; Feng, Zichao; Chen, Anjing; Li, Wenjie; Zhang, Qing; Wang, Jian; Huang, Bin; Li, Xingang
Highlights : Melatonin elevates miR-6858-5p level of GBM cells. Melatonin inhibit GBM progression through miR-6858-5p/SIRT3/AKT signaling pathway. Melatonin inhibits growth of GBM cells in vivo. Abstract: MicroRNAs (miRNAs), small non-coding RNA molecules with a length of 18–25 nucleotides, have been shown to be involved in mediating various malignant properties of GBM, including growth, invasion and angiogenesis. Here, we investigated whether miRNAs might be involved in mediating the suppression of malignant properties of GBM by melatonin (MEL), an amine hormone secreted by the pineal gland. Sequencing was performed to screen specifically for miRNAs induced by MEL in U87 and an orthotopically xenografted primary GBM cell line, GBM#P3. MiR-6858-5p was the most significantly up-regulated miR in GBM cell lines in response to MEL ( 5 × ). Transfection of a mimic of miR-6858-5p into both cell lines led to a decrease in viability of 50% at 72 h, confirming a suppressive role for miR-6858-5p in GBM. In contrast, an inhibitor of miR-6858-5p rescued GBM cells from MEL suppression of proliferation, migration and invasion. Analysis using Targetscan yielded candidate mRNAs targeted by miR-6858-5p, some of which are involved in the SIRT/AKT signaling pathway. In cells transfected with a mimic or an inhibitor of miR-6858-5p, levels of SIRT3 and downstream components of the AKT signaling pathway were suppressed or up-regulated, respectively, both in vitro and in an in vivo orthotopic xenograft model. Our results elucidated a novel molecular mechanism underlying MEL suppression of GBM, highlighting a role for miRNAs, and provide a potential therapeutic strategy for GBM.